Kapitał własny w procesie finansowania działalności małego i średniego przedsiębiorstwa - Stoga, Ewa (Basic Capital in Small and Medium-Sized Enterprises, 2005)
It is known that on average small and medium-sized enterprises constitute 99,9 of the total number of businesses and their manpower represents 75 of all employees. Enterprises of this size traditionally face undercapitalisation. The undercapitalisation determines their credit worth and their ability to obtain banking and non-banking forms of financing. This article presents main problems and difficulties that this sector meets with limited possibilities of building own basic capital.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 140-150